Titanium dioxide composite sunscreen material based on silicon microspheres and preparation method thereof

CN119868172BActive Publication Date: 2026-10-27GUANGDONG PHARMA UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510082980.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-18
Publication Date
2026-10-27
Estimated Expiration
2045-01-18

AI Technical Summary

Technical Problem

[0004]本发明的目的在于提供一种基于硅微球改性的二氧化钛复合防晒材料及其制备方法,成倍提升复合防晒材料的UVB波段的吸收值,且肤感轻盈,有效克服了纳米二氧化钛肤感差、纳米粒径小导致安全性差等缺点

Benefits of technology

[0035]本发明以高表面电荷的良好分散性的二氧化硅微球(SNS)为载体,通过有效调控二氧化硅微球(SNS)表面上二氧化钛的负载量与形态,进而调控复合防晒材料的防晒效果,得到基于硅微球改性的二氧化钛复合防晒材料(SNS@TiO2),其制备方法操作简单,绿色环保。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119868172B_ABST
    Figure CN119868172B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of cosmetics, and discloses a titanium dioxide composite sunscreen material based on silicon microspheres and a preparation method thereof. The monodisperse silicon dioxide microspheres with high surface charge are used as carriers, and a certain amount of titanium dioxide is uniformly distributed on the surface of the silicon dioxide microspheres. The silicon dioxide microspheres are combined with the titanium dioxide, which not only doubles the absorption value of the UVB band of the composite sunscreen material, but also makes the skin feel light, increases the particle size, and has high safety. The application overcomes the shortcomings of poor skin feel of nano-titanium dioxide and poor safety caused by small nano-particle size, and has the advantages of light skin feel, good sunscreen performance, low cost, good biocompatibility and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cosmetic technology, and in particular to a titanium dioxide composite sunscreen material based on silicon microsphere modification and its preparation method. Background Technology

[0002] Titanium dioxide (TiO2) is one of the only physical sunscreens currently approved for use in my country. It is a broad-spectrum sunscreen that has a strong shielding ability against UVB (280-320nm) and also protects against UVA (320-400nm). It also has stable chemical properties, antibacterial properties, UV reflection, non-toxicity, and high transparency. It is gentle and non-irritating to the skin, and therefore is widely used as an additive in sunscreen cosmetics.

[0003] Although titanium dioxide has outstanding applications in the field of sun protection, it still has certain drawbacks in practical use: First, as a physical sunscreen agent, titanium dioxide needs to be used at a concentration of 10%-20% to provide good sun protection, which will form a thick white coating with a noticeable "fake white" feeling. It also has disadvantages such as poor dispersibility, occlusion, and poor skin feel, which can easily lead to "white sweat" or oily and non-breathable skin. Second, nano-titanium dioxide has a small particle size, usually 1nm-100nm, while the diameter of human pores is about 6μm. Using cosmetics containing nano-titanium dioxide can easily cause pore blockage, adverse reactions such as inhalation or penetration into skin tissue, and promote skin inflammation. It is also not easily excreted with sweat, posing certain safety risks during use. Summary of the Invention

[0004] The purpose of this invention is to provide a titanium dioxide composite sunscreen material based on silicon microsphere modification and its preparation method, which significantly improves the UVB absorption value of the composite sunscreen material and has a lightweight feel, effectively overcoming the shortcomings of nano-titanium dioxide, such as poor skin feel and poor safety due to small nanoparticle size. By loading titanium dioxide onto the surface of silicon dioxide microspheres (SNS) with good dispersion of high surface charge, it has advantages such as lightweight feel, good sun protection performance, low cost, and good biocompatibility.

[0005] To achieve the above objectives, the technical solution of the present invention is as follows:

[0006] On the one hand, the present invention provides a titanium dioxide composite sunscreen material based on silicon microsphere modification, wherein the titanium dioxide composite sunscreen material based on silicon microsphere modification uses monodisperse silicon dioxide microspheres with high surface charge as a carrier, and titanium dioxide is uniformly distributed and loaded on the surface of the silicon dioxide microspheres.

[0007] Furthermore, the silica microspheres are submicron particles with a particle size of approximately 300-450 nm.

[0008] Furthermore, the particle size of the titanium dioxide composite sunscreen material based on silicon microsphere modification is approximately 300-500 nm.

[0009] Furthermore, the dispersibility of the silica microspheres is 0.2-0.3.

[0010] Furthermore, the titanium dioxide composite sunscreen material based on silicon microsphere modification is uniformly loaded with titanium dioxide on the surface of the silicon dioxide microspheres, and the loading amount of the metallic element titanium is 1.0-6.5 wt%.

[0011] Secondly, the present invention also provides a method for preparing the aforementioned titanium dioxide composite sunscreen material based on silicon microsphere modification, comprising the following steps:

[0012] S1. Provide silica microspheres, wherein the silica microspheres are monodisperse silica microspheres with high surface charge, and are prepared by reacting citric acid, ammonia, tetraethyl orthosilicate and solvent as raw materials;

[0013] S2. Preparation of a titanium dioxide composite sunscreen material based on silicon microsphere modification, which is prepared by reacting the silicon dioxide microspheres, ammonia, ethyl acetate and tetrabutyl titanate as raw materials.

[0014] Furthermore, the preparation steps of the silica microspheres include:

[0015] S11. Citric acid and ethanol are mixed to obtain solution A. Solution A is then mixed with ammonia water and reacted to obtain solution B. Tetraethyl orthosilicate is mixed with ethanol and reacted to obtain solution C.

[0016] S12. Solution C is added dropwise to solution B. After reacting for a period of time, suspension D is obtained. After centrifugation, washing and drying, silica microspheres are obtained.

[0017] Furthermore, the amount of citric acid added is 0.2g, and the amount of anhydrous ethanol is 100mL;

[0018] Preferably, the concentration of the ammonia water is 25% and the amount added is 24 mL;

[0019] Preferably, the reaction time between solution A and ammonia is 0.5 h; preferably, the amount of tetraethyl orthosilicate added is 9 mL, and the amount of anhydrous ethanol added is 50 mL.

[0020] Preferably, the reaction time of the tetraethyl orthosilicate and ethanol is 0.5 h;

[0021] Preferably, the reaction time between solution C and solution B is 2.5 hours;

[0022] Preferably, the drying temperature is 55℃-80℃.

[0023] Furthermore, the preparation steps of the titanium dioxide composite sunscreen material based on silicon microsphere modification include:

[0024] S21. The silica microspheres are mixed with ammonia water to obtain suspension E. After centrifugation, a white precipitate F is obtained. Then, the white precipitate F is mixed with ethyl acetate to obtain suspension G.

[0025] S22. Tetrabutyl titanate and ethyl acetate are mixed to obtain solution H. Then solution H is mixed with suspension G and reacted to obtain suspension I. After filtration, washing and drying, titanium dioxide composite sunscreen material based on silicon microsphere modification is obtained.

[0026] Furthermore, the amount of silica microspheres added is 1.2g, the concentration of ammonia water is 0.6mol / L, and the amount added is 12mL;

[0027] Preferably, the reaction time of the silica microspheres and ammonia is 15 minutes.

[0028] Preferably, the white precipitate F is mixed with 38 mL of ethyl acetate;

[0029] Preferably, the amount of tetrabutyl titanate added is 0.6 mL and the amount of ethyl acetate added is 2 mL;

[0030] Preferably, the solution H and suspension G are mixed and reacted for 3 hours;

[0031] Preferably, the drying temperature is 105°C.

[0032] This invention first uses citric acid (CA), ammonia (NH3·H2O), and tetraethyl orthosilicate (TEOS) as raw materials to prepare silica microspheres (SNS) with high surface charge and good dispersibility via chemical precipitation. During the synthesis process, citric acid and ammonia are introduced to form a buffer pair, creating a suitable pH environment for the formation of monodisperse silica microspheres. Simultaneously, a certain amount of carboxyl groups are introduced onto the surface of the silica microspheres (SNS), resulting in high surface charge. Furthermore, the repulsive effect between surface charges contributes to the excellent dispersibility of the silica microspheres (SNS). The entire preparation process is simple, energy-efficient, and environmentally friendly.

[0033] Secondly, in an alkaline environment, silica microspheres (SNS) and dispersion medium (ethyl acetate) are in a suspension system composed of "SNS + ethyl acetate". At the "solid / liquid" interface, tetrabutyl titanate undergoes a hydrolysis reaction, and the generated Ti(OH)4 is loaded on the surface of silica microspheres. After high-temperature drying, titanium dioxide is loaded on the surface of silica microspheres, resulting in a titanium dioxide composite sunscreen material (SNS@TiO2) modified with silica microspheres. Specifically, this invention utilizes highly active carboxyl groups introduced onto the surface of silica microspheres (SNS) as active sites. In a suspension system composed of "SNS + ethyl acetate", the hydroxyl groups in Ti(OH)4 generated by the hydrolysis of tetrabutyl titanate at the "solid / liquid" interface combine with the hydroxyl groups on the surface of silica microspheres (SNS) through condensation polymerization. Ti(OH)4 is deposited a second time on the surface of silica microspheres (SNS). At the same time, by adjusting appropriate alkaline conditions, the condensation polymerization process can be made more stable, so that the Ti(OH)4 generated by the hydrolysis of tetrabutyl titanate is relatively uniformly loaded on the surface of silica microspheres (SNS). After washing and high-temperature drying, titanium dioxide is loaded on the surface of silica microspheres (SNS), resulting in a titanium dioxide composite sunscreen material (SNS@TiO2) modified with silica microspheres.

[0034] The beneficial effects of this invention are:

[0035] This invention uses silica microspheres (SNS) with high surface charge and good dispersibility as a carrier. By effectively controlling the loading and morphology of titanium dioxide on the surface of silica microspheres (SNS), the sun protection effect of the composite sunscreen material is controlled, resulting in a titanium dioxide composite sunscreen material (SNS@TiO2) modified with silica microspheres. The preparation method is simple, green and environmentally friendly.

[0036] This invention relates to a silicon microsphere-modified titanium dioxide composite sunscreen material (SNS@TiO2). By combining silicon dioxide microspheres (submicron particles with a diameter of 300-500 nm) with titanium dioxide, the refractive index of titanium dioxide is increased, thereby improving sunscreen performance. This not only improves skin feel but also increases particle size, resulting in high safety. It offers advantages such as a lightweight feel, excellent sun protection, low cost, and good biocompatibility, overcoming the disadvantages of titanium dioxide, such as poor skin feel and safety due to small nanoparticle size. It provides a lightweight feel, is thin and not bulky, while retaining good sun protection performance, meeting user needs. When the titanium loading in the silicon microsphere-modified titanium dioxide composite sunscreen material (SNS@TiO2) is approximately 6.5 wt%, its sun protection performance is nearly 15 times higher than traditional sunscreens (such as pure TiO2), exhibiting high physicochemical stability and excellent overall performance. Attached Figure Description

[0037] Figure 1These are SEM images of the SNS and SNS@TiO2 of this invention;

[0038] Figure 2 These are the infrared spectra of SNS, TiO2, and SNS@TiO2 of this invention;

[0039] Figure 3 These are the XRD patterns of SNS, TiO2, and SNS@TiO2 of this invention;

[0040] Figure 4 These are the UV spectra of SNS, SNS@TiO2, and TiO2 of this invention;

[0041] Figure 5 These are the UV spectra of SNS@TiO2 prepared with different amounts of tetrabutyl titanate according to the present invention;

[0042] Figure 6 This is a schematic diagram of particle size analysis of SNS@TiO2 prepared with different ammonia concentrations according to the present invention. Detailed Implementation

[0043] The embodiments of the present invention will be described in detail below.

[0044] The specific implementation steps of this invention are divided into two steps:

[0045] S1. Provide silica microspheres, wherein the silica microspheres are monodisperse silica microspheres with high surface charge, and are prepared by reacting citric acid, ammonia, tetraethyl orthosilicate and solvent as raw materials;

[0046] S2. Preparation of a titanium dioxide composite sunscreen material based on silicon microsphere modification, which is prepared by reacting the silicon dioxide microspheres, ammonia, ethyl acetate and tetrabutyl titanate as raw materials.

[0047] First, silica microspheres (SNS) were prepared using citric acid (CA), ammonia (NH3·H2O), and tetraethyl orthosilicate (TEOS) as raw materials. During the synthesis process, citric acid and ammonia formed a buffer pair, creating a suitable alkaline environment that facilitated the relatively controllable hydrolysis reaction of TEOS, resulting in silica microparticles with moderate particle size and good dispersibility. Second, a silica-microsphere-modified titanium dioxide composite sunscreen material, SNS@TiO2, was synthesized. In a suspension system composed of SNS and ethyl acetate, under weakly alkaline conditions at the solid / liquid interface, the carboxyl groups on the surface of the silica microspheres acted as active sites, condensing with the hydroxyl groups in Ti(OH)4 to form Ti(OH)4, which was then deposited onto the surface of the silica microspheres. After washing and high-temperature drying, the Ti(OH)4 was transformed into TiO2-loaded silica microspheres, thus preparing the silica-microsphere-modified titanium dioxide composite sunscreen material SNS@TiO2.

[0048] Example 1

[0049] This embodiment provides silica microspheres (SNS) and their preparation method, the specific steps of which include:

[0050] 1) Dissolve 0.2g of citric acid in 100mL of anhydrous ethanol to obtain solution A;

[0051] 2) Dissolve 24 mL of ammonia water (25 wt%) in solution A and react for 0.5 h to obtain solution B;

[0052] 3) Dissolve 9 mL of tetraethyl orthosilicate in 50 mL of anhydrous ethanol and react for 0.5 h to obtain solution C;

[0053] 4) Add solution C dropwise to solution B and react for 2.5 hours to obtain suspension D;

[0054] 6) Centrifuge suspension D at 8000 r / min, wash twice with 100 mL of pure water and once with 100 mL of anhydrous ethanol, and dry at 80 °C to obtain silica microspheres, which are then stored for later use.

[0055] Example 2

[0056] This embodiment provides silica microspheres (SNS) and their preparation method. The specific steps are basically the same as in Example 1, except that the amount of citric acid is changed. The specific steps are as follows:

[0057] 1) Dissolve 0.4g of citric acid in 100mL of anhydrous ethanol to obtain solution A;

[0058] The resulting suspension D was centrifuged, washed, and dried at 55°C to obtain silica microspheres, which were then stored for later use.

[0059] Example 3

[0060] This embodiment provides silica microspheres (SNS) and their preparation method. The specific steps are basically the same as in Example 1, except that the amount of citric acid is changed. The specific steps are as follows:

[0061] 1) Dissolve 0.6g of citric acid in 100mL of anhydrous ethanol to obtain solution A;

[0062] The resulting suspension D was centrifuged, washed, and dried at 65°C to obtain silica microspheres, which were then stored for later use.

[0063] Examples 1-3 above all produced silica microspheres (SNS) with moderate particle size and good dispersibility. The silica microspheres are submicron particles with a particle size of about 300-450 nm and a dispersibility of 0.2-0.3. A certain amount of carboxyl groups were introduced on the surface of the silica microspheres (SNS) to give them high surface charge. Furthermore, the repulsive effect between surface charges gives the silica microspheres (SNS) good dispersibility. The entire preparation process is simple, energy-efficient, and environmentally friendly.

[0064] Example 4

[0065] This embodiment provides a titanium dioxide composite sunscreen material SNS@TiO2 based on silicon microsphere modification and its preparation method, the specific steps of which include:

[0066] 1) Disperse 1.2g of silica microspheres SNS (using Example 1 as an example) in 12mL of 0.1M ammonia water (i.e., the concentration of ammonia water is 0.1mol / L), stir and react for 15min to obtain suspension E;

[0067] 2) Centrifuge the suspension E at 5000 r / min to remove the ammonia solution and obtain a relatively moist white precipitate F;

[0068] 3) Add the white precipitate F to 38 mL of ethyl acetate to obtain solution G;

[0069] 4) Dissolve 0.6 mL of tetrabutyl titanate in 2 mL of ethyl acetate to obtain solution H;

[0070] 5) Add solution H to solution G and stir for 3 hours to obtain suspension I;

[0071] 6) Filter the suspension I, wash it twice with 100 mL of pure water, wash it once with 100 mL of anhydrous ethanol, and dry it at 105 °C to obtain the titanium dioxide composite sunscreen material SNS@TiO2 based on silicon microsphere modification.

[0072] Example 5

[0073] This embodiment provides a titanium dioxide composite sunscreen material SNS@TiO2 based on silicon microsphere modification. The specific steps are basically the same as in Example 4, except that the ammonia concentration is changed. The specific steps are as follows:

[0074] 1) Disperse 1.2g of SNS in 12mL of 0.2M ammonia solution and stir for 15min to obtain suspension E.

[0075] Example 6

[0076] This embodiment provides a titanium dioxide composite sunscreen material SNS@TiO2 based on silicon microsphere modification. The specific steps are basically the same as in Example 4, except that the ammonia concentration is changed. The specific steps are as follows:

[0077] 1) Disperse 1.2g of SNS in 12mL of 0.4M ammonia solution and stir for 15min to obtain suspension E.

[0078] Example 7

[0079] This embodiment provides a titanium dioxide composite sunscreen material SNS@TiO2 based on silicon microsphere modification. The specific steps are basically the same as in Example 4, except that the ammonia concentration is changed. The specific steps are as follows:

[0080] 1) Disperse 1.2g of SNS in 12mL of 0.6M ammonia solution and stir for 15min to obtain suspension E.

[0081] Example 8

[0082] This embodiment provides a titanium dioxide composite sunscreen material SNS@TiO2 based on silicon microsphere modification. The specific steps are basically the same as in Example 4, except that the ammonia concentration is changed. The specific steps are as follows:

[0083] 1) Disperse 1.2g of SNS in 12mL of 0.8M ammonia solution and stir for 15min to obtain suspension E.

[0084] Example 9

[0085] This embodiment provides a titanium dioxide composite sunscreen material SNS@TiO2 based on silicon microsphere modification. The specific steps are basically the same as in Example 4, except that the ammonia concentration is changed. The specific steps are as follows:

[0086] 1) Disperse 1.2g of SNS in 12mL of 1.0M ammonia solution and stir for 15min to obtain suspension E.

[0087] Example 10

[0088] This embodiment provides a titanium dioxide composite sunscreen material SNS@TiO2 based on silicon microsphere modification. The specific steps are basically the same as in Example 7, except that the amount of tetrabutyl titanate is changed. The specific steps are as follows:

[0089] 4) Dissolve 0.05 mL of tetrabutyl titanate in 2 mL of ethyl acetate to obtain solution H.

[0090] Example 11

[0091] This embodiment provides a titanium dioxide composite sunscreen material SNS@TiO2 based on silicon microsphere modification. The specific steps are basically the same as in Example 7, except that the amount of tetrabutyl titanate is changed. The specific steps are as follows:

[0092] 4) Dissolve 0.1 mL of tetrabutyl titanate in 2 mL of ethyl acetate to obtain solution H.

[0093] Example 12

[0094] This embodiment provides a titanium dioxide composite sunscreen material SNS@TiO2 based on silicon microsphere modification. The specific steps are basically the same as in Example 7, except that the amount of tetrabutyl titanate is changed. The specific steps are as follows:

[0095] 4) Dissolve 0.2 mL of tetrabutyl titanate in 2 mL of ethyl acetate to obtain solution H.

[0096] Example 13

[0097] This embodiment provides a titanium dioxide composite sunscreen material SNS@TiO2 based on silicon microsphere modification. The specific steps are basically the same as in Example 7, except that the amount of tetrabutyl titanate is changed. The specific steps are as follows:

[0098] 4) Dissolve 0.3 mL of tetrabutyl titanate in 2 mL of ethyl acetate to obtain solution H.

[0099] Example 14

[0100] This embodiment provides a titanium dioxide composite sunscreen material SNS@TiO2 based on silicon microsphere modification. The specific steps are basically the same as in Example 7, except that the amount of tetrabutyl titanate is changed. The specific steps are as follows:

[0101] 4) Dissolve 0.4 mL of tetrabutyl titanate in 2 mL of ethyl acetate to obtain solution H.

[0102] Example 15

[0103] This embodiment provides a titanium dioxide composite sunscreen material SNS@TiO2 based on silicon microsphere modification. The specific steps are basically the same as in Example 7, except that the amount of tetrabutyl titanate is changed. The specific steps are as follows:

[0104] 4) Dissolve 0.6 mL of tetrabutyl titanate in 2 mL of ethyl acetate to obtain solution H.

[0105] The silicon microsphere-modified titanium dioxide composite sunscreen materials prepared in Examples 4-15 above use monodisperse silicon dioxide microspheres with high surface charge as a carrier, and titanium dioxide is uniformly distributed and loaded on the surface of the silicon dioxide microspheres. The particle size of the silicon microsphere-modified titanium dioxide composite sunscreen material is about 300-500 nm, and the loading amount of titanium dioxide and the loaded metal element titanium in the silicon microsphere-modified titanium dioxide composite sunscreen material is 1-6.5 wt%. Because Examples 4-15 exemplarily studied the effects of tetrabutyl titanate dosage, ammonia concentration, etc. on the performance of SNS@TiO2, the titanium element content corresponding to Example 15 is 6.5%, and the preferred dosage of tetrabutyl titanate is 0.6 mL; when the dosage of tetrabutyl titanate is greater than 0.6 mL, the skin feel of the product deteriorates significantly, and when the dosage of tetrabutyl titanate is less than 0.1 mL, the UVB absorption value of the product is too low.

[0106] The present invention tests the SNS and SNS@TiO2 prepared in the above embodiments:

[0107] The composite sunscreen material SNS@TiO2 was formulated into a suspension of appropriate concentration, and its sunscreen performance was determined by ultraviolet spectrophotometer.

[0108] From the appendix Figure 1 It can be seen that SNS and SNS@TiO2 are spherical at the microscopic level. SNS@TiO2 also has titanium metal attached to its surface, with a particle size of approximately 400 nm. Compared with SNS, SNS@TiO2 is basically a regular sphere, indicating that SNS@TiO2 has a good skin feel, being soft and delicate.

[0109] From the appendix Figure 2 It can be seen that TiO2 has a bending vibration peak of Ti-OH at 1441 cm-1, while SNS@TiO2 has a stronger intensity at 1445 cm-1 compared to SNS. SNS@TiO2 also has an absorption peak at 928 cm-1, while SNS has no absorption peak in this range. The above indicates that a bonding reaction occurs between TiO2 and SiO2, and Ti-O-Si bonds are formed, thus obtaining the composite sunscreen material SNS@TiO2.

[0110] From the appendix Figure 3As can be seen from the XRD patterns of SNS, TiO2, and SNS@TiO2, red represents SiO2, blue represents SNS@TiO2, and black represents the self-made TiO2. PDF#21-1272 is the standard card for traditional pure TiO2. The XRD pattern of pure TiO2 shows the specific lattice peaks corresponding to traditional pure TiO2. However, no lattice peaks corresponding to traditional pure TiO2 were found in the XRD pattern of SNS@TiO2. This proves that secondary deposition occurred on the surface of silica microspheres, and titanium dioxide was loaded onto the surface of the silica microspheres as a new phase, resulting in a new phase different from traditional pure TiO2. Thus, SNS@TiO2 with excellent sun protection properties was prepared.

[0111] Appendix Figure 4 The meaning of "SNS-1.0" is: the amount of SNS sample used during the test is 1.0 mg / mL. (See attached document.) Figure 4 It can be seen that when the absorbance of the sample SNS@TiO2 is at least higher than 1 in the UVB band (280-320nm) and at least higher than 0.5 in the UVA band (320-400nm), the sample is considered to have sun protection properties. In a 0.5% chitosan solution prepared with 0.1% glacial acetic acid as the solvent... Figure 4 In the diagram, 1.0 represents a test concentration of 1 mg / mL, and 0.065 represents 0.065 mg / mL. These values ​​represent the test concentrations of SNS, TiO2, and SNS@TiO2 for each sample. By comparing the same level of sun protection performance at the same concentration, it is demonstrated that pure SNS has no significant impact on the sun protection performance of the sample (SNS@TiO2) and is not the cause of improved sun protection. Furthermore, at the same concentration (1 mg / mL) of SNS, TiO2, and SNS@TiO2, the sun protection performance of the sample (SNS@TiO2) is comparable to that of TiO2. However, the actual titanium loading of the sample (SNS@TiO2) is only 6.5 wt%, or 1 mg. The SNS@TiO2 sample contains 0.065 mg of pure TiO2. The concentration of titanium dioxide (0.065 mg / mL) was obtained at the same dilution factor. By comparing the sun protection performance and concentration of the same level and content of titanium dioxide, it was found that 1 mg of the sample (SNS@TiO2) uses less titanium dioxide (0.065 mg) but has the same sun protection performance as 1 mg of pure titanium dioxide, achieving a 15.4-fold improvement in sun protection performance.

[0112] Appendix Figure 5 All samples used in the tests were composite sunscreen materials. The term "0.6-1.0" means that, for example, the sample from Example 15 was used during testing. The amount of tetrabutyl titanate used in synthesis was 0.6 mL, and the sample volume used in the test was 1.0 mg / mL, corresponding to the label "0.6-1.0". (See attached...) Figure 5and attached Figure 6 It is known that when the absorbance of the SNS@TiO2 sample is at least higher than 1 in the UVB band (280-320nm) and at least higher than 0.5 in the UVA band (320-400nm), the sample is considered to have sun protection properties. In a 0.5% chitosan solution prepared with 0.1% glacial acetic acid as a solvent, when the sample concentration is 1 mg / mL, for example, SNS@TiO2 prepared with 0.6 mL of tetrabutyl titanate exhibits high absorbance, and preferably, ammonia concentration, low PDI value, and relatively uniform particle size distribution of approximately 400 nm. In a suspension system composed of SNS and ethyl acetate, under weakly alkaline conditions, at the solid / liquid interface, the carboxyl active groups on the surface of silica microspheres serve as active sites. The hydroxyl groups in Ti(OH)4 condense and combine with the carboxyl active groups, resulting in a secondary deposition of Ti(OH)4 onto the silica microsphere surface. After washing and high-temperature drying, it transforms into a TiO2-loaded composite sunscreen material, SNS@TiO2. Due to the highly active carboxyl groups on the surface of the SNS silica microspheres, adjusting the ammonia concentration to create a suitable pH environment is beneficial for generating SNS@TiO2 with a more uniform particle size distribution, better dispersibility, and more uniform particle size. The sunscreen performance of the sample (SNS@TiO2) can be improved by increasing the loading of titanium dioxide on the silica microsphere surface by changing the amount of tetrabutyl titanate. By changing the ammonia concentration, the weakly alkaline ammonia solution facilitates the hydrolysis of tetrabutyl titanate during the formation of SNS@TiO2, while also promoting the combination of Ti(OH)4 with the active carboxyl groups on the silicon microspheres, resulting in a sample with a relatively uniform particle size (SNS@TiO2).

[0113] Simultaneously, this invention measures the ductility of pure TiO2 and SNS@TiO2. Specifically, 1.5g of composite sunscreen material (SNS@TiO2) powder is placed in a 4cm diameter circle in the center of a glass plate. A 1kg glass is placed on the glass plate for five minutes, and the diameter change is recorded. The ductility is then measured, and a skin feel test is performed. The test results are shown in the table below:

[0114] Table 1 shows the test results of the ductility measurement.

[0115]

[0116] The extensibility test of the above samples was measured 3 times. The "diameter" mentioned above actually refers to the "extensibility diameter" of the sample after it was spread out during the extensibility test. Analyzing the data in Table 1, we can see that: (1) Because the particle size of traditional pure TiO2 is small, the average extensibility diameter of the sample measured in the extensibility test was 5.20 cm, and its actual skin feel evaluation was: astringent, obstructive when applied, and poor skin feel. (2) However, the actual skin feel evaluation of the SNS@TiO2 sample prepared in this invention (exemplary example 15) was: soft and light on the skin, and easy to spread. This is mainly because: in the extensibility test, the average extensibility diameter of the SNS@TiO2 sample was 5.50 cm. Although the difference between the test value of the pure TiO2 sample and the SNS@TiO2 sample was only 0.3 cm, the difference in actual skin feel evaluation was obvious: pure TiO2 had a frictional feel and was relatively astringent; while SNS@TiO2 was soft, had no astringent feel, was smooth when applied to the skin, comfortable to the skin, and had improved extensibility. Therefore, the significant difference in skin feel between pure TiO2 and SNS@TiO2 can be attributed to the preparation of uniformly distributed titanium dioxide loading on the surface of silica microspheres through secondary hydrolysis at the interface of SNS microspheres using a heterogeneous reaction system.

[0117] The above are merely specific embodiments of the present invention and are not intended to limit the scope of protection of the present invention; any substitutions and improvements made without departing from the concept of the present invention shall fall within the scope of protection of the present invention.

Claims

1. A titanium dioxide composite sunscreen material based on modified silicon microspheres, characterized in that, The modified titanium dioxide composite sunscreen material based on silica microspheres uses monodisperse silica microspheres with high surface charge as a carrier, on which titanium dioxide is uniformly distributed and loaded. The silica microspheres are submicron particles with a particle size of 300-450 nm. The particle size of the modified titanium dioxide composite sunscreen material based on silica microspheres is 300-500 nm. The dispersibility of the silica microspheres is 0.2-0.

3. The modified titanium dioxide composite sunscreen material based on silica microspheres uses titanium dioxide uniformly distributed and loaded on the surface of the silica microspheres, and the loading amount of the metallic element titanium is 1-6.5 wt%. The monodisperse silica microspheres with high surface charge are prepared by reacting citric acid, ammonia, tetraethyl orthosilicate, and solvent as raw materials. The modified titanium dioxide composite sunscreen material based on silica microspheres is prepared by reacting the silica microspheres, ammonia, ethyl acetate, and tetrabutyl titanate as raw materials.

2. A method for preparing the titanium dioxide composite sunscreen material based on silicon microsphere modification as described in claim 1, characterized in that, Includes the following steps: S1. Provide silica microspheres, wherein the silica microspheres are monodisperse silica microspheres with high surface charge, and are prepared by reacting citric acid, ammonia, tetraethyl orthosilicate and solvent as raw materials; S2. Preparation of a titanium dioxide composite sunscreen material based on silicon microsphere modification, which is prepared by reacting the silicon dioxide microspheres, ammonia, ethyl acetate and tetrabutyl titanate as raw materials.

3. The preparation method of the titanium dioxide composite sunscreen material based on silicon microsphere modification as described in claim 2, characterized in that, The preparation steps of the silica microspheres include: S11. Citric acid and ethanol are mixed to obtain solution A. Solution A is then mixed with ammonia water and reacted to obtain solution B. Tetraethyl orthosilicate is mixed with ethanol and reacted to obtain solution C. S12. Solution C is added dropwise to solution B. After reacting for a period of time, suspension D is obtained. After centrifugation, washing and drying, silica microspheres are obtained.

4. The preparation method of the titanium dioxide composite sunscreen material based on silicon microsphere modification as described in claim 3, characterized in that, The amount of citric acid added is 0.2-0.6g, and the amount of anhydrous ethanol is 100mL; The concentration of the ammonia solution is 25% and the amount added is 24 mL; The reaction time between solution A and ammonia water is 0.5 hours; The amount of tetraethyl orthosilicate added is 9 mL, and the amount of anhydrous ethanol added is 50 mL. The reaction time for the tetraethyl orthosilicate and ethanol mixture is 0.5 h. The reaction time between solution C and solution B is 2.5 hours. The drying temperature is 55℃-80℃.

5. The preparation method of the titanium dioxide composite sunscreen material based on silicon microsphere modification as described in claim 2, characterized in that, The preparation steps of the titanium dioxide composite sunscreen material based on silicon microsphere modification include: S21. The silica microspheres are mixed with ammonia water to obtain suspension E. After centrifugation, a white precipitate F is obtained. Then, the white precipitate F is mixed with ethyl acetate to obtain suspension G. S22. Tetrabutyl titanate and ethyl acetate are mixed to obtain solution H. Then solution H is mixed with suspension G and reacted to obtain suspension I. After filtration, washing and drying, titanium dioxide composite sunscreen material based on silicon microsphere modification is obtained.

6. The preparation method of the titanium dioxide composite sunscreen material based on silicon microsphere modification as described in claim 5, characterized in that, The silica microspheres were added in an amount of 1.2g, and the ammonia solution was added in a concentration of 0.1-1mol / L in a volume of 12mL. The reaction time between the silica microspheres and ammonia water is 15 minutes. The white precipitate F was mixed with 38 mL of ethyl acetate; The amount of tetrabutyl titanate added is 0.05-0.6 mL, and the amount of ethyl acetate added is 2 mL; The solution H and suspension G are mixed and reacted for 3 hours; The drying temperature is 105°C.

Citation Information

Patent Citations

  • Nanometer silicon dioxide and titanium dioxide compound microparticle and preparation method thereof

    CN101624188A

  • Preparation method for core-shell TiO2-SiO2 microsphere self-assembled structural color film

    CN106423000A

  • Monodisperse silicon microsphere modification-based zinc oxide sunscreen material and preparation method thereof

    CN118873422A